Oxytocin and Cortisol Levels in Dog Owners and Their Dogs Are Associated with Behavioral Patterns: An Exploratory Study - Petersson, Maria; Uvnäs-Moberg, Kerstin; Nilsson, Anne; Gustafson, Lise-Lotte; Hydbring-Sandberg, Eva; Handlin, Linda (Frontiers in Psychology, 2017)
We have previously shown that dog–owner interaction results in increasing oxytocin levels in owners and dogs, decreasing cortisol levels in owners but increasing cortisol levels in dogs. The present study aimed to further investigate whether oxytocin and cortisol levels in the previously tested owners and dogs were associated with their behaviors during the interaction experiment. Ten female volunteer dog–owners and their male Labrador dogs participated in a 60 min interaction experiment with interaction taking place during 0–3 min and blood samples for analysis of oxytocin and cortisol were collected at 0, 1, 3, 5, 15, 30, and 60 min. The entire experiment was videotaped and the following variables were noted; the different types (stroking, scratching, patting and activating touch, i.e., scratching and patting combined) as well as the frequency of touch applied by the owner, the number of times the owner touched her dog, the dog’s positions and time spent in each position. Correlations were analyzed between the behavioral variables and basal oxytocin levels, maximum oxytocin levels, delta oxytocin levels, basal cortisol levels and cortisol levels at 15 min. Owners with low oxytocin levels before and during the interaction touched their dogs more frequently (0 min: Rs = -0.683, p = 0.042; oxytocin maximum: Rs = -0.783, p = 0.013). The lower the dogs’ oxytocin levels during the interaction, the more stroking they received (Rs = -0.717, p = 0.041). The more frequently activating touch was applied by the owner, the higher the dogs’ cortisol levels became (15 min: Rs = 0.661, p = 0.038). The higher the owners’ maximum oxytocin level the fewer position changes the dogs made (Rs = -0.817, p = 0.007) and the shorter time they spent sitting (Rs = -0.786, p = 0.036), whereas the higher the owners’ basal cortisol levels, the longer time the dogs spent standing (0 min: Rs = 0.683, p = 0.041). In conclusion, oxytocin and cortisol levels, both in dogs and in their owners, are associated with the way the owners interact with their dogs and also with behaviors caused by the interaction.